Dampak Penerapan Sistem Blok terhadap Kepuasan Mahasiswa Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Medan - Putri Anita Lumbantoruan; Marta Marta; Adnan Sitompul; Agil Badawi; Zulkarnian Siregar (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Universities are required to develop learning models that support effective learning processes and ensure student satisfaction. Medan State University has implemented a block system that organizes learning into intensive periods focusing on a single course at a time. This study aims to determine the effect of the block system on student satisfaction in the Management Department, Faculty of Economics. This research employed a quantitative approach using a structured questionnaire distributed to 50 students who participated in block-system learning. The instrument was validated and tested for reliability before use. Data were analyzed through descriptive statistics and simple linear regression after fulfilling classical assumption tests. The results show that all questionnaire items were valid and reliable, and the regression model met the assumptions of normality, homoscedasticity, and non-autocorrelation. Regression analysis indicates that the block system has a positive and significant effect on student satisfaction, expressed in the equation Y = 2.817 + 1.013X. The coefficient of determination (R² = 0.859) demonstrates that the block system explains 85.9% of the variation in student satisfaction. These findings confirm that the block system contributes meaningfully to improving focus, comprehension, and learning experience, which lead to higher satisfaction among Management students at Medan State University.